Template synthesis of defect-rich MoS2-based assemblies as electrocatalytic platforms for hydrogen evolution reaction. Issue 14 (29th January 2019) - Kagkoura, Antonia; Tzanidis, Iordanis; Dracopoulos, Vassilios; Tagmatarchis, Nikos; Tasis, Dimitrios
Abstract : Template-assisted growth of defect-rich MoS2 nanostructures gave rise to enhanced hydrogen evolution reaction activity. Abstract : Defect-rich MoS2 nanostructures were synthesized in solution by a microwave-assisted process, employing either a sacrificial soft template (CaCO3 ) or a non-sacrificial hard template (graphene oxide) and the electrocatalytic performance towards the hydrogen evolution reaction was found to be superior for the latter.